SISTEM INFORMASI PENGELOLAAN DATA MASYARAKAT BERBASIS WEBSITE (STUDI KASUS PKK KECAMATAN CIMAHI SELATAN) - Sarah Fadilah Sulaeman; Dahlan (Universitas Lampung, 2025)
In the digital era, effective data management has become a crucial need, particularly in the field of social and community empowerment. In Cimahi Selatan District, the Family Welfare Empowerment (PKK) organization plays a significant role in collecting community data to support the planning and implementation of welfare programs. However, the current manual data recording process presents several challenges, such as data duplication, delayed reporting, and a high risk of recording errors. To address these issues, a web-based Community Data Management Information System was developed to automate the processes of data entry, processing, and reporting, making them more efficient, accurate, and structured. This system is expected to enhance the work effectiveness of PKK administrators and support more data-driven, targeted decision-making. The system was developed using the Waterfall model approach, while testing was conducted using Blackbox and User Acceptance Testing (UAT) methods. The test results show that the system functions properly. In UAT, the system achieved a user satisfaction rate of 90.27%, indicating that it met the required criteria in terms of functionality and performance. Therefore, this information system can make a significant contribution to improving data management and supporting PKK programs in Cimahi Selatan District.